The leaf-mining genus Lyonetia Hübner from China, with descriptions of two new species (Lepidoptera: Yponomeutoidea: Lyonetiidae) - Liu, Shiyu; Liu, Tengteng; Yu, Jiazhi; Xu, Jiasheng; Teng, Kaijian (Zootaxa, 2023)
So far, only five species of the genus Lyonetia Hübner, 1825 have been recorded in China. In this paper, we describe two new species: L. (Lyonetiola) blasta T. Liu, sp. n., and L. (Lyonetiola) duplistriata T. Liu, sp. n., and report a newly recorded species, L. (Lyonetia) ledi Wocke, 1859 from China. Autumnal forms, manifesting darker forewings, of L. (Lyonetia) clerkella (Linnaeus, 1758) were collected from Xizang at an altitude of 3650 m in summer. The distribution and host plants of L. (Lyonetia) clerkella (Linnaeus, 1758) and L. (Lyonetia) prunifoliella (Hübner, 1796) in China are summarized. Photos of adults, male and female genitalia are provided. Host plants, leaf mines and DNA barcodes are also provided when available.